Child protection on educational rights in Zanzibar in relation to poverty - Hamdan, Sikujua Omar; Che Soh @ Yusoff, Roslina (Faculty of Law, Universiti Teknologi MARA, 2016)
In Zanzibar, educational right is guaranteed under Zanzibar Constitution, and also under Zanzibar Education Act no.6 of 1982 inconformity with the United Nation’s Convention on the Rights of the Child 1989. However, poverty is a main contributing factor and the main reason toward the inadequate educational rights protection in Zanzibar. Many people in Zanzibar live below standard of life, they cannot afford the school fees payments, hence the children become victims. The government of Zanzibar initiates various programmes and set aside resources for the implementation of child educational right. Nevertheless, it is evident that the impact is not been effective. Education is not affordable because quality education is expensive for children who live below standard. Such children are therefore vulnerable and deprived. Due to the prevailing poor economic conditions, many families continue to live in severe poverty. The reasons of writing this paper are; to discuss the inadequacy of educational rights protection and difficulties in accessing a quality education due to poverty in Zanzibar, to highlight the government’s efforts in combating poverty by organizing different programmes and the extents of the effectiveness of the programmes organized to reduce such poverty so as the educational rights should be adequately protected. The paper involved an exploratory legal research, therefore it employ an analyses of both primary and secondary documented data. The findings show that the government policies and effort on education is inadequate and therefore there is a need to reform the whole educational system to ensure the success welfare of children of getting a quality education is preserved.